2022
DOI: 10.2106/jbjs.rvw.21.00185
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Megaprostheses in Nononcologic Lower-Extremity Total Joint Arthroplasty

Abstract: As the number of primary total joint arthroplasty (TJA) procedures continues to rise, megaprostheses have found an emerging role in more complex revision arthroplasty cases that require additional reconstruction, stability, and restoration of function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…The risk of poor bone health is a major concern for orthopaedic surgery. Patients with osteoporosis or other bone-related conditions are at higher risk of postoperative fractures and adverse surgical outcomes 2,9,[26][27][28][29][30][31][32] . For example, Lindenberg-Larsen et al found that patients with osteoporosis were at increased risk of periprosthetic femoral fracture when undergoing THA 9 .…”
Section: Surgical Risks Associated With Poor Bone Healthmentioning
confidence: 99%
“…The risk of poor bone health is a major concern for orthopaedic surgery. Patients with osteoporosis or other bone-related conditions are at higher risk of postoperative fractures and adverse surgical outcomes 2,9,[26][27][28][29][30][31][32] . For example, Lindenberg-Larsen et al found that patients with osteoporosis were at increased risk of periprosthetic femoral fracture when undergoing THA 9 .…”
Section: Surgical Risks Associated With Poor Bone Healthmentioning
confidence: 99%
“…Each available surgical procedure has advantages and disadvantages regarding bone preservation, surgical timing, and complexity. For instance, PFR in nononcological salvage procedures has become increasingly popular; however, it has been associated with a reoperation rate of 20.3% and high complication rates 4,5 . Femoral IG with a cemented stem has been linked with good long-term outcomes with an 84.2% 10-year survival rate free of reoperation 6 .…”
mentioning
confidence: 99%
“…In addition, as the number of revision total knee arthroplasty has continued to increase, surgeons are progressively using more megaprosthesis for nononcological cases 2,3 . Nevertheless, despite numerous advances in prosthetic design, which have allowed for optimized longevity, early weight-bearing, and rapid restoration of function after megaprosthetic distal femoral replacement (DFR), failure rates remain high 2 . Furthermore, a systematic review compiled survival rates for rotating-hinge DFR and found a survival of 78.6%, 77.7%, 70.9%, 48.7%, and 42.2% at years 5, 10, 15, 20, and 25, respectively 4 .…”
mentioning
confidence: 99%
“…Limb salvage surgery, including a megaprosthesis or endoprosthetic replacement, is one of the mainstream reconstruction treatments when possible 1 . In addition, as the number of revision total knee arthroplasty has continued to increase, surgeons are progressively using more megaprosthesis for nononcological cases 2,3 . Nevertheless, despite numerous advances in prosthetic design, which have allowed for optimized longevity, early weight-bearing, and rapid restoration of function after megaprosthetic distal femoral replacement (DFR), failure rates remain high 2 .…”
mentioning
confidence: 99%